Status of Lithuanian fighters of freedom according international law and cases of MGB agents strikers - Žilinskas, Justinas (Genocidas ir rezistencija, 2004)
According to international conventions, partisan resistance should be interpreted as an exercise of a state’s right to self–defence, one of the oldest institutes in international law. Despite the failure by the Republic of Lithuania to form a real government-in-exile recognised abroad, which would have fully represented the occupied nation (there was a diplomatic service and the Supreme Committee for the Liberation of Lithuania), the aims of the partisan movement (to restore Lithuania’s independence and democratic order), its scale and the support it had from the people suggest that it was the leadership of the partisan movement which was the highest legitimate political and military authority in Lithuania. Having concluded that the Lithuanian partisans were combatants, legitimate participants in hostilities from the point of view of the international law of armed conflict, the approach to be applied to interpretation of actions by agents–hitmen according to the criteria of this law must be examined. In summary, the methods of combat used by agents–hitmen constitute deception from the point of view of the international law of armed conflict, and, since deception is prohibited by international law, the persons who use it must be considered to be committing a war crime, that is to say, an act in violation of the laws and customs of war, for which liability is stipulated under both international and domestic law.
Keywords: partizans; international law; repressive structures; repressions; agents